Self-powered, ultra-high detectivity and high-speed near-infrared photodetectors from stacked–layered MoSe2/Si heterojunction. (24th November 2020) - Xu, Yan; Ma, Yuanming; Yu, Yongqiang; Chen, Shirong; Chang, Yajing; Chen, Xing; Xu, Gaobin
Abstract: Photodetectors based on high-performance, two-dimensional (2D) layered transition metal dichalcogenides (TMDCs) are limited by the synthesis of larger-area 2D TMDCs with high quality and optimized device structure. Herein, we report, for the first time, a uniform and stacked–layered MoSe2 film of high quality was deposited onto Si substrate by using the pulsed laser deposition technique, and then in situ constructed layered MoSe2 /Si 2D–3D vertical heterojunction. The resultant heterojunction showed a wide near-infrared response up to 1550 nm, with both ultra-high detectivity up to 1.4 × 10 14 Jones and a response speed approaching 120 ns at zero bias, which are much better than most previous 2D TMDC-based photodetectors and are comparable to that of commercial Si photodiodes. The high performance of the layered MoSe2 /Si heterojunction can be attributed to be the high-quality stacked–layered MoSe2 film, the excellent rectifying behavior of the device and the n-n heterojunction structure. Moreover, the defect-enhanced near-infrared response was determined to be Se vacancies from the density functional theory (DFT) simulations. These results suggest great potential of the layered MoSe2 /Si 2D–3D heterojunctions in the field of communication light detection. More importantly, the in situ grown heterojunctions are expected to boost the development of other 2D TMDCs heterojunction-based optoelectronic devices.